Synthesis of cocoa butter equivalent from palm oil by Carica papaya lipase-catalyzed interesterification - Porntippa Pinyaphong (2018)
Cocoa butter equivalent could be synthesized by lipase-catalyzed interesterification of oil. The objective of this research was to investigate the synthesis of cocoa butter equivalent from interesterification of palm oil catalyzed by Carica papaya lipase. The study showed that the compositions of cocoa butter equivalent were affected by acyl donor sources, substrate ratio, initial water of enzyme, reaction time, reaction temperature and the amount of enzyme. Among three acyl donors tested (methyl stearate, ethyl stearate and stearic acid), methyl stearate appeared to be the best acyl donor for the synthesis of cocoa butter equivalent from palm oil catalyzed by C. papaya lipase. The best reaction conditions were: substrate ratio (palm oil: methyl stearate, mol/mol) at 1: 4, water activity of enzyme at 0.11, reaction time at 4 h, reaction temperature at 45oC and 18% by weight of the enzyme. The chemical and physical properties of cocoa butter equivalent were 9.75 ± 0.41% free fatty acid, 44.89 ± 0.84 iodine number, 193.19 ± 0.78 sponification value and melting point at 37-39oC. The yield of cocoa butter equivalent was 55% based on palm oil used.